A case-control study of sleep disturbances in pediatric obsessive-compulsive disorder. (April 2018) - Jaspers-Fayer, Fern; Lin, Sarah Yao; Belschner, Laura; Mah, Janet; Chan, Elaine; Bleakley, Clare; Ellwyn, Rhonda; Simpson, Annie; McKenney, Katherine; Stewart, S. Evelyn
Highlights: 72% of pediatric OCD participants versus 15% of controls reported disturbed sleep. Disorders of initiation and maintaining sleep (DIMS) are common in pediatric OCD. In contrast to adult OCD, delayed sleep phase disorder (DSPD) is not highly prevalent. Abstract: Background: Sleep disturbances, including delayed sleep phase disorder (DSPD) and disorders of sleep initiation and maintenance (DIMS), have repeatedly been identified in adult obsessive-compulsive disorder (OCD). These disturbances have not been well-characterized objectively in pediatric OCD. Methods: Thirty OCD-affected youth (8–18 yrs, 40% male) and 30 age and gender-matched healthy controls (HCs) completed the Sleep Disturbances Scale for Children (SDSC), and one week of continuous actigraphy with concurrent sleep diary documentation. A subsample completed the Children's Sleep Hygiene Scale (CSHS) and Sleep Attitudes and Beliefs Scale (SABS). Results: Seventy-two percent of OCD participants reported sleep disturbances versus 15% of HC participants ( p  < 0.001). Convergent actigraphy results suggested DIMS but not DSPD were common. Discussion: The parents of OCD-affected children seem to be successfully controlling bedtimes, preventing circadian rhythm system disruptions. OCD status does adversely impact, however, the perisleep arousal system. These results have important clinical implications, suggesting sleep problems may be best managed through direct treatment of OCD symptoms. It is recommended that all pediatric OCD patients be screened for sleep disturbances to inform treatment plan development.